Comparison of Survival Analysis of COVID-19 Patients with Known Diabetes - Bashir, Saira; Malik, Sarwar; Khan, Gohar; ul Islam, Fasih (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare the survival rate of COVID-19 patients with diabetes versus without diabetes COVID-19 patients. Study Design: Comparative, prospective study. Place and Duration of Study: The patients were selected from the special ward established for COVID-19 patients came in Federal Government Polyclinic Hospital, Islamabad Pakistan, from Dec 2020 to May 2021. Methodology: 50 without diabetes (control) and 50 with diabetes (study) confirm cases of COVID-19 patients, who fulfill the inclusion and exclusion criteria, were included in the study through consecutive sampling. Independent sample t test, chi square test and Kaplan-Meire survival analysis was used to compile the results. Results: Out of 100 majority 75 patients were male. The average age of the patients was 52.08±14.85 years. Both the groups were equal with respect of gender with p-value >0.05. The average age of the patient was significantly higher in study group with p-value <0.001. Overall percentage of patients of oxygen dependency, mechanical ventilation required, and use of Angiotension receptor inhibitor were higher in study group as compared to the control group patients with p-value <0.001. The survival rate was lower in study group as compared to the control group but the difference was not significant with pvalue >0.05. Conclusion: The COVID-19 patients with diabetes, need extra care and attention before and after infection in the current COVID-19 pandemic. They are at higher risk and with respect of prolong hospital stay due to severe attack of COVID-19 and also higher risk of mortality too.